The public health implications of telematic technologies: An exploratory qualitative study in the UK. (March 2020) - Green, Judith; Romanovitch, Andrey; Garnett, Emma; Steinbach, Rebecca; Lewis, Daniel
Abstract: Introduction: Reducing motorised transport is crucial for achieving public health goals, but cars will continue to be essential for many in the medium term. The role of emerging technologies in mitigating the public health disadvantages of this private car use has been under-examined to date. Telematics are increasingly used by novice drivers in the UK to reduce insurance premiums. An exploratory study of novice drivers' experiences of telematics identified implications for public health that warrant urgent further research. Methods: An exploratory qualitative study, using semi-structured interviews with 12 drivers aged 17–25 in three regions of the UK (Aberdeenshire, Hertfordshire and London). Results: Telematics were acceptable to young drivers, and reported to mitigate some negative health consequences of driving (injury risks, over-reliance on car transport), without reducing access to determinants of health such as employment or social life. However, there were suggestions that those at higher risk were less likely to adopt telematics. Conclusion: Market-based mechanisms such as telematics are potential alternatives to well-evaluated policy interventions such as Graduated Driver Licensing for reducing road injury risks for novice drivers, with a different mix of risks and benefits. However, claims to date from insurance companies about the contribution of telematics to public health outcomes should be evaluated carefully to account for biases in uptake.